Improving Local Educational Services with Distance Education: The Case of Tepebaşı City Institute - Aydın Ziya Özgür; İlker Kayabaş (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
Municipalities, one of the most important elements of local governments in Türkiye, are among the leading organizations that conduct intensive educational activities, apart from institutions whose main function is education, such as the Ministry of National Education and higher education institutions. Local educations organized by municipalities and mostly aimed at helping the personal, social, and professional development of the local people appeal to a very wide audience of millions varying in age, education status, social status, disability status, and more. Considering its sphere of influence, it is thought that local education services conducted by municipalities assume an important role within the Turkish education system. Based on this assumption, the City Institute Project was initiated in collaboration with Anadolu University and the Tepebaşı Municipality of Eskişehir. Within the scope of the project, the structure of educational services carried out by local governments, its place in national education policies, and its sphere of influence were first investigated. In line with the findings obtained, 10 new courses were prepared based on a teaching model designed to support and improve local educational services with distance education. The prepared courses were made available to the masses via the Tepebaşı City Institute Lifelong Learning Portal, which was developed from scratch for the needs of the project and were evaluated according to the opinions of the students. In summary, this study examined the role and impact of local educational services within the scope of national education policies, based on the findings and results obtained from the Tepebaşı City Institute Project. Additionally, experiences related to how distance education theory could be utilized to improve local educational services were shared.